The Effect of Bending Selection for Restrain Load Analysis Crude Oil Pipeline at Pig Launcher Area - Aswin, Aswin; Wicaksono, Mohamad Bayu; Wicaksana, Dewana Aryalintang (JMES The International Journal of Mechanical Engineering and Sciences, 2024)
Bending on the pipeline has a major influence on the value of the restrain load that occurs in the pipeline system in the pig launcher area. This study aims to evaluate the effect of the selection of bends on the pipeline to restrain the pipeline. Large load restrains on pipeline restraints often occur in the pig launcher area resulting from the selection of bend pipes. Restrain load analysis is carried out to ensure that the selection of pipeline bending does not result in a large load to reduce system failure in operating conditions. The working design pressure is 680 psi with a design temperature of 130 F. Analysis of the pipeline restrain load system using CAESAR II software to see the most effective bending angle comparison to use. The results of the analysis show that the impact of selecting a bending pipeline in the pig launcher area greatly affects the value of the load restrain that occurs. The selection of bending by using a varied bending angle in the pipeline system is able to reduce the Restrain load that occurs. From the results of selecting the bending pipeline system, the bending angle of 90 degrees has the smallest load restrain value in every axis, the use of 30 degrees bend has the largest load restrain value in the X axis, and the use of 45 degrees bend has the largest load restrain value in the Y axis and Z axis